Bilateral laparoscopic ureterolysis using hydrodissection in retroperitoneal fibrosis: a new application of an old technique - Abdessater, Maher (Res Rep Urol, 2019)
Objective: To describe our new laparoscopic approach in ureterolysis using the ERBEJET(®) 2 device to hydrodissect the ureters in idiopathic retroperitoneal fibrosis. Methods: Bilateral laparoscopic ureterolysis was done after medical therapy failure (steroids) in a 47 year old patient with retroperitoneal fibrosis. Ureteral stents were placed before surgery. Only five trocars were used for both sides, Toldt’s fascia was opened and the dissection was performed till the psoas muscle. The ureters were completely freed from the fibrotic tissue using the ERBEJET 2 device (pure hydrodissection). An omental wrap was passed behind the colonic flexure at the right and placed around the ureter. At the left, we closed Toldt’s fascia by running sutures back to the freed ureter. Results: The operating time was 198 mins. The blood loss was 50 cc. The hospital stay was 3 days. The double J stents were removed at 4 weeks postoperatively. After 2 years, the patient is free of symptoms with normal creatinine level and no urinary tract obstructions. Conclusions: Hydrodissection of the ureter in retroperitoneal fibrosis is a new application in the upper urinary tract laparoscopic approach that has not been described in literature before. It seems to offer excellent midterm outcomes. The use of ERBEJET 2 device seems to simplify the procedure and make it feasible and safe (less trauma to the ureter and more conservation of its blood supply). We believe that comparative studies are needed to assess the role of hydrodissection in ureterolysis for retroperitoneal fibrosis.